Tradition and colloquialism: A reading to understand the development of Nicanor Parra´s poetry in four poetry books - Galindo Gonzales, Sara Gabriela (2021)
This article studies the interaction between tradition and colloquialism in Cancionero sin nombre (1937), Poemas y Antipoemas (1954), La cueca Larga (1958) and Manifiesto (1963) by Nicanor Parra. These texts are studied considering Belic's proposals in Verso español y verso europeo regarding free verse. Likewise, we apply what Antonio Quilis points out in Métrica española for the metrical and rhythmic analysis of the selected poems. The hypothesis of this article is that both colloquialism and tradition converge in the free verse advocated by the Chilean poet. In this sense, this paper present, first, a general approach to Nicanor Parra's work, followed by a comparative analysis of the poetry books and, finally, the conclusions.